Knowledge, attitudes and practices regarding oral care for patients with endotracheal tube among critical care nurses in Hospital Universiti Sains Malaysia - Ngazuddin, Muhammad Iqbal (2020)
Oral care practice is essential in improving patients’ comfort and when performed effectively can prevents oral infection. Providing oral care to patient is one of the fundamental in nursing practice and if ignored, could poses a threat to patients especially those with endotracheal intubation and ventilation. The aim of this study was to assess nurse’s level of knowledge, attitude, and practice regarding oral care for patient with endotracheal tube in ICU, Hospital Universiti Sains Malaysia. A cross sectional study was used involving 32 ICU nurses in Hospital Universiti Sains Malaysia. Convenience sampling was used as a sampling method for this study. Data were collected by structured questionnaire which consist of four sections evaluating nurses’ knowledge, attitudes, and practices of oral care for intubated patients and acquiring nurses’ demographic information. The average percentage ICU nurses’ knowledge, attitudes, and practices of oral care for intubated patients were 54.2%, 92.8%, and 57.8%, respectively. This study showed that ICU nurses’ knowledge about oral care was associated with nurses’ oral care performance in term of frequency (p = 0.009). Nurses learn more about oral care from nursing school which may contribute to the increase in frequency of nurses providing oral care for their patients (p = 0.001). Guidance from experienced senior ICU nurses also contribute to better oral care practice in ICU (p = 0.014). the findings of this study show that nurses who acquire more relevant source of learning about oral care have a higher knowledge about oral care practice and it may affect their practice of providing oral care for intubated patients.